Silencing of miR169a improves drought stress by enhancing vascular architecture, ROS scavenging, and photosynthesis of Solanum tuberosum L - Lei, Ziqian; Zhang, Xingyuan; Wang, Ming; Mao, Jun; Hu, Xinxi; Lin, Yuan; Xiong, Xingyao; Qin, Yuzhi (Frontiers in Plant Science, 2025)
Vascular bundles regulate water balance, nutrient uptake and transport, and stress responses, ultimately influencing the yield and quality of crops. However, our understanding of the genetic functions of microRNAs (miRNAs) during vascular development remains limited. In this research, the role of miR169a in potatoes was studied. Silencing StmiR169a in potatoes promoted vascular bundle formation, resulting in not only upright and robust stems but also longer roots and more extensive root systems. Histological analysis revealed a significant increase in the number of xylem vessels in the vascular bundles of stems and roots of RNAi-mediated miR169a lines (STTM169). Silencing miR169a led to higher water use efficiency, enhanced photosynthesis rates, elevated enzymatic antioxidant activity, and reduced levels of reactive oxygen species (ROS), thereby enhancing the drought resistance of potatoes. However, overexpression of miR169a lines (OE169a) showed the opposite effects. The nuclear factor Y subunit NF-YA3 was identified as a target gene of StmiR169a. The miR169a/NF-YA3 module may be involved in the regulation of potato vascular bundle development and the response to drought stress.